Tiapride in levodopa-induced involuntary movements. - Lees, A J (1979)
Tiapride, a substituted benzamide derivative closely related to metoclopramide, reduced levodopa-induced peak dose involuntary movements in 16 patients with idiopathic Parkinson's disease. However, an unacceptable increase in disability from Parkinsonism with aggravation of end-of-dose akinesia led to its cessation in 14 patients. Tiapride had no effect on levodopa-induced early morning of "off-period" segmental dystonia. These results fail to support the notion that levodopa-induced dyskinesias are caused by overstimulation of a separate group of dopamine receptors.